1997
DOI: 10.1046/j.1365-313x.1997.11051095.x
|View full text |Cite
|
Sign up to set email alerts
|

Starch synthesis in amyloplasts purified from developing potato tubers

Abstract: SummaryAmyloplasts have been purified from potato tubers by mechanical homogenization and gravity sedimentation through Nycodenz. Based on the recovery and latency of organelle-specific marker enzymes, the recovery of amyloplasts is approximately 13%, exhibiting 65% intactness, with less than 1% contamination by other subcellular fractions. These preparations were able to synthesize starch from glucose-l-phosphate plus ATP, or ADP-glucose but not from glucose-6-phosphate. Rates of starch synthesis from glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 27 publications
(55 reference statements)
4
31
0
Order By: Relevance
“…1c) (Pozueta-Romero et al 1991, Naeem et al 1997, Shannon et al 1998. Essentially in line with previous investigations describing the occurrence of cyclic gluconeogenic processes in bacteria (Gaudet et al 1992, Belanger and Hatfull 1999, Guedon et al 2000 and animals (David et al 1990, Massillon et al 1995, Bollen et al 1998 in which glycogen synthesis and degradation take place simultaneously, active turnover of starch has been shown to occur in non-photosynthetic tissues of plants (Pozueta-Romero and Akazawa 1993, Neuhaus et al 1995, Sweetlove et al 1996b.…”
Section: Introductionsupporting
confidence: 72%
“…1c) (Pozueta-Romero et al 1991, Naeem et al 1997, Shannon et al 1998. Essentially in line with previous investigations describing the occurrence of cyclic gluconeogenic processes in bacteria (Gaudet et al 1992, Belanger and Hatfull 1999, Guedon et al 2000 and animals (David et al 1990, Massillon et al 1995, Bollen et al 1998 in which glycogen synthesis and degradation take place simultaneously, active turnover of starch has been shown to occur in non-photosynthetic tissues of plants (Pozueta-Romero and Akazawa 1993, Neuhaus et al 1995, Sweetlove et al 1996b.…”
Section: Introductionsupporting
confidence: 72%
“…This raises the question whether or not Glc-1-P directly enters the chloroplasts where the starch synthesis takes place. Until now, Glc-1-P has not been reported to be imported into chloroplasts, but indirect evidence for an uptake by nongreen plastids has been published (for potato tubers, Kosegarten and Mengel, 1994;Naeem et al, 1997; for wheat [Triticum aestivum], Tetlow et al, 1996; for soybean [Glycine max], Coates and ap Rees, 1994). To answer the question mentioned above, chloroplasts isolated from Arabidopsis leaves were incubated with [U-14 C]Glc-1-P. As a control, an aliquot of the same chloroplast preparation was mechanically broken by using a potter and, subsequently, the homogenate was treated identically.…”
Section: Utilization Of External Glc-1-p By Isolated Arabidopsis Chlomentioning
confidence: 99%
“…The import of Glc-1-P into intact amyloplasts isolated from tubers or suspension-cultured cells from potato has been reported (Kosegarten and Mengel, 1994;Naeem et al, 1997), but the uptake of this sugar phosphate by intact cells has not been demonstrated so far. To gain further insight into this uptake process, 14 C-labeling experiments were performed with tuber discs that were incubated with several 14 C-labeled sugars or sugar derivatives, such as Suc, Glc, or Glc-1-P, both in the presence and absence of unlabeled sugar compounds (Fig.…”
Section: Selective Uptake Of Glc-1-p By Tuber Discsmentioning
confidence: 99%